Persepsi Masyarakat terhadap Pengelolaan Taman Nasional Batang Gadis, Kabupaten Mandailing Natal, Provinsi Sumatera Utara - Dini Novalanty Ohara Daulay; Jafron Wasiq Hidayat (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Successful management of a national park cannot be separated from the role of government as the manager. Communities as partners of the government also have important contribution in the area management. Arising problems in the national park area are generally caused by disharmony relationship between the communities and the area manager. Communities support around national park through communities participation in the area management is necessary to preserve the sustainability of national park forest area. A variety of perception and involvement all stakeholders should be known to accommodate the interests of all stakeholders, so overlapping interests that harming one of the stakeholders can be avoided. Batang Gadis National Park (BGNP) is one of the national parks in Indonesia. To strengthen institutional BGNP Authority as area manager, this research is considered important to do. With communities perceptions to BGNP, expected to provide inputs for improvement of the BGNP management. This research aimed to know communities perceptions about BGNP management. The research is carried out on July 2017 at Sirambas Village. This qualitative research is conducted by interviewing informants who have been determined i.e. government official, village representative institution, public figure/religious figure, and communities. In addition to interview, researcher also observate, so the information obtained is suitable to the statement submitted with the reality in the field. Selection of informants in this research using non probability sampling method, i.e. purposive sampling method. The selected informants are people who are considered to have information or knowledge related to research object i.e. conservation sector. Furthermore, data are analyzed in a descriptive. The results showed that the communities perceptions of Sirambas Village to BGNP can be categorized into medium perception.